Controllable synthesis of monodisperse nonspherical colloidal particles with cavity structures. Issue 15 (24th June 2019) - Sun, Yangyi; Zhang, Hua; Han, Weichang; Huang, Huajun; Qi, Dongming
ABSTRACT: This article reports a facile controllable approach to prepare monodisperse nonspherical colloidal particles with cavity structures by one‐pot soap‐free emulsion polymerization of styrene (St), 3‐(trimethoxysilyl)propyl methacrylate (MPS), and acrylic acid (AA). In our strategy, only by varying the feeding time of AA to the as‐polymerized St and MPS, the nonspherical latex particles with single cavity of different surface roughness and multicavity structures could be successfully synthesized. The depth and width of the cavity can be also easily controlled by adjusting the amount of MPS and AA. A possible formation mechanism is proposed on the basis of experimental results. These nonspherical colloidal particles, which have controllable cavity structures, are good building blocks or templates for the construction of functional coating and complex colloidal architectures. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1645–1652 Abstract : Monodisperse nonspherical colloidal particles with cavity structures are controllably synthesized by one‐pot soap‐free emulsion polymerization, only by varying the feeding time of acrylic acid (AA) to the as‐polymerized styrene (St) and 3‐(trimethoxysilyl)propyl methacrylate (MPS). The depth and width of the cavity can also be easily controlled by adjusting the amount of MPS and AA.